PENINGKATAN KEMAMPUAN SOSIAL EMOSIONAL ANAK MELALUI KEGIATAN MEMBACA BUKU CERITA DI TK DEVI AULIA - Endang Sari, Mega; Faridatul Ula; Imamah (Jurnal Tawadhu, 2025)
This study aims to explore the impact of storybook reading activities on the social-emotional development of early childhood learners at TK Devi Aulia. Using a qualitative descriptive approach through literature review, this research examines previous studies, journals, and books related to storytelling and its educational benefits. The findings reveal that reading storybooks not only enhances children’s linguistic abilities but also fosters empathy, emotional regulation, and positive social interaction. Story-based learning helps children recognize and manage emotions, build caring relationships, and develop moral values through narrative experiences. Furthermore, teachers play a crucial role in guiding discussions, modeling emotional expression, and creating a warm classroom atmosphere. In conclusion, storybook reading serves as an effective pedagogical tool to strengthen children’s emotional intelligence, empathy, and cooperative behavior in early childhood education settings.